Fabrication and non-destructive testing of composite materials - Muhammad Izzuan Jamal (2018)
There has been an increase in the usage of composites in recent times. Aerospace, automotive and even marine industries are using composites. New generation composites, like the fibre metal laminate (FML), have been developed for the aerospace industry and are being used in the A380. The FML used in A380 is called glass reinforced aluminium (GLARE). Common issues with FML include cracks and voids, which can be developed during the production process, as well as when used in an application. Conventional ultrasonic testing can be performed to locate the defects present. In this project, the knowledge of FML is applied, resulting in the combination of carbon fibre and aluminium being introduced as the FML. The report presents the results obtained from the ultrasonic A-scan performed on different specimens such as aluminium, carbon fibre composite, and FML. The method of interpreting and understanding the signals on the A-scan was explored on the aluminium and carbon fibre composite first, before performing on the FML. In this manner, there is an opportunity to gain the basic knowledge needed on the individual materials before proceeding to the FML specimen. Several types of transducers and couplants were also used to determine their advantages and disadvantages. Properties such as material velocity, attenuation, and transmission and reflection of medium were also obtained from the experiments. Defects were also fabricated so that it could be located after the ultrasonic A-scan has been conducted. The different types of ultrasonic A-scan technique such as pulse-echo, and through transmission were conducted using the USM 35X DAC ultrasonic equipment. It is important to study the ultrasonic A-scan of FML so that it can be further applied for future use.